2015
DOI: 10.1016/j.ajpath.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Keratan Sulfate Epitope Elicits in Central Nervous Tissues of Transgenic Model Mice and Patients with Amyotrophic Lateral Sclerosis

Abstract: The functional role of 5D4 antibody-reactive keratan sulfate (KS) in the pathogenesis of neurodegenerative diseases is unknown. We therefore studied the expression of 5D4-reactive KS in amyotrophic lateral sclerosis (ALS), a motor neuron-degenerative disease, with the use of SOD1(G93A) ALS model mice and patients with ALS. Histochemical and immunoelectron microscopic characterizations showed that the 5D4-reactive KS is expressed in Mac2/galectin-3-positive activated or proliferating microglia of SOD1(G93A) ALS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 62 publications
0
51
0
Order By: Relevance
“…The expression of 5D4‐KSPG in microglia differs significantly between strains of inbred rats (Jander & Stoll, ). In mammals, a subpopulation of 5D4‐KSPG‐expressing microglia was also reported in the spinal cord and retina (Bertolotto et al , , ; Jander & Stoll, ; Jones & Tuszynski, ; Zhang et al , ; Foyez et al , ). The 5D4‐KSPG‐microglia exhibit a preferential regional distribution in the CNS.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The expression of 5D4‐KSPG in microglia differs significantly between strains of inbred rats (Jander & Stoll, ). In mammals, a subpopulation of 5D4‐KSPG‐expressing microglia was also reported in the spinal cord and retina (Bertolotto et al , , ; Jander & Stoll, ; Jones & Tuszynski, ; Zhang et al , ; Foyez et al , ). The 5D4‐KSPG‐microglia exhibit a preferential regional distribution in the CNS.…”
Section: Introductionmentioning
confidence: 90%
“…The 5D4‐KSPG‐microglial population described above is influenced by pathology. In particular, 5D4‐KSPG expression is increased selectively in a subset of IBA1/CD11b‐positive microglia in the SOD1 G93A mouse model and human cases of amyotrophic lateral sclerosis (ALS; Hirano et al , ; Foyez et al , ), and in a Wallerian degeneration mouse model of spinal cord injury (Shinjo et al , ), while it decreases in a Guillain–Barré syndrome rat model of experimental autoimmune neuritis (Matsui et al , ). Mice deficient in N‐acetylglucosamine 6‐O‐sulfotransferase‐1 (GlcNAc6ST‐1), an enzyme involved in 5D4‐KSPG biosynthesis, also show reduced 5D4‐KSPG expression in the CNS (Zhang et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…) showing that KS restricts spinal cord repair (Foyez et al . ). GlcNAc6ST‐1 is required for KS biosynthesis in the CNS (Zhang et al .…”
Section: Kspgs Of the Cns/pnsmentioning
confidence: 97%
“…Four biochemical pathways seemed to represent the most consistent changes at a proteomic level: metabolism of carbohydrates (p= 0.0099), glycosaminoglycans (GAGs) metabolism, lysosome (p= 0.0015), synthesis of phosphatidic acid (p= 0.0184) and wnt signalling pathway (p= 0.0337). It has been shown that GAGs are involved in protein aggregation and prion diffusion ( [36][37][38][39][40][41][42][43][44] ). Lysosome activity changes were described in ALS caused by the C9orf72 gene repeat expansions ( [45][46][47][48][49] ), while synthesis of PA is linked to all types of phospholipids, including phosphatidylcholine and phosphatidylethanolamine that have been linked to ALS and prion disease pathogenesis ( 50,51 ).…”
Section: Functional Analysismentioning
confidence: 99%